Comparison Between Opioid Free Anesthesia and Opioid Based Anesthesia in Laparoscopic Hysterectomy: A Systematic Review - Mahesa Putra, Ode; I Ngurah Arya Wicaksana (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Introduction: In Gynecology field, laparoscopy surgery is used for many procedures that were traditionally performed via laparotomy. Hysterectomy associated with postoperative pain, which greatly affected postoperative recovery and patient satisfaction. Combinations of opiod base analgesia (OBA) and opioid free analgesia (OFA) agents are combined with local or regional anesthesic techniques whenever possible. Methods: A systematic search of relevant databases was conducted to identify case control studies comparing OBA and OFA post hysterectomy procedure. Inclusion criteria encompassed studies reporting Visual Analog Scale (VAS) and Numeric Rating Scale (NRS) as an outcome measure. Quality assessment and data extraction were performed independently by author. Results: The systematic review identified a total of four case-control studies meeting the inclusion criteria with total of 357 patients undergone hysterectomy procedure. The sample sizes varied across the studies, with the smallest study including 30 patients and the largest study including 157 patients. The outcomes were assessed using VAS and NRS scores. The results consistently showed that either OBA or OFA administration giving similar outcome on pain scale. Conclusion: All studies concluded whether OBA or OFA administration peri or postoperative given similar or not significantly different of pain scoring outcomes. Although OFA would give a better result to maintain post operative nausea and vomitting (PONV) and reducing opiod-related adverse events that happen postoperatively.